MOTORBIKE PURCHASE AT PT FIF SYARIAH BANDA ACEH BASED ON LOCAL ACT 11 OF 2018 CONCERNING ISLAMIC FINANCIAL LAW - Muhammad Kalkausar (JURISTA: Jurnal Hukum dan Keadilan, 2018)
The Ba'i Murabahah agreement is one of the transaction contracts in buying and selling which is carried out in the form of accounts payable as an example in financing. PT FIF Syariah Banda Aceh branch is one of the non-bank financial institutions that provides financing services to the community specifically on AHM products. Qanun No. 11 of 2018 concerning Sharia Financial Institutions is one of the regulations that determine how practices in muamalah transactions are in accordance with Islamic principles. This study aims to examine how the application of the dictums of the non-cash motorbike purchase financing agreement at PT FIF Syariah, Banda Aceh branch after the implementation of Qanun LKS No. 11 of 2018? And how is the review of the Ba'i Murabahah contract on the clauses and dictums of the motorbike purchase financing agreement at PT FIF Syariah, Banda Aceh branch after the implementation of Qanun LKS No. 11 of 2018? This research uses qualitative research methods with a normative juridical approach, data collection techniques in the form of contract documentation. . The research results of the analysis of the financing agreement contract at PT FIF Syariah, Banda Aceh branch that have been carried out show that the application of the dictum of the agreement that has been applied is in accordance with the provisions contained in the Qanun LKS, in its application the management of PT FIF Syariah prioritises the agreement of the consumer before continuing the contract. The clauses and dictums of the agreement that have been contained in the agreement contract at PT FIF Syariah, Banda Aceh branch have also fulfilled the legal conditions of sale and purchase in the form of a ba'i murabahah contract, including legal subjects, clear object descriptions, price transparency and profit margin acquisition, costs, determination of fines and authorisation of fiduciary guarantees.